2018
DOI: 10.3168/jds.2018-14408
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous identification of bovine and equine DNA in milks and dairy products inferred from triplex TaqMan real-time PCR technique

Abstract: Koumiss is a popular dairy product in many lands, traditionally prepared from mare milk with spontaneous fermentation. Mare milk and its fermented derivates are more expensive than cow milk and its fermented derivates, and the possibility exists for producers and dealers to adulterate equine products with bovine items. In this work, we described the development of a triplex real-time PCR based on species-specific TaqMan probes for identification of bovine and equine DNA in milks and dairy products. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…DNA from meat and dairy products was isolated with TaKaRa MiniBEST Universal Genomic DNA Extraction Kit, using a modified CTAB method (Guo et al., 2018). DNA concentration and quality were assessed using a NanoDrop 2000c at a wavelength of 260 nm and 280 nm.…”
Section: Methodsmentioning
confidence: 99%
“…DNA from meat and dairy products was isolated with TaKaRa MiniBEST Universal Genomic DNA Extraction Kit, using a modified CTAB method (Guo et al., 2018). DNA concentration and quality were assessed using a NanoDrop 2000c at a wavelength of 260 nm and 280 nm.…”
Section: Methodsmentioning
confidence: 99%
“…A triplex real-time PCR was recently developed for the identification of bovine and equine DNA by employing developed primers and probes. The limits of detection of the method were 0.001 ng for milk and yogurt and 0.005 ng for sour soup and koumiss, respectively [ 128 ].…”
Section: Dairy Productsmentioning
confidence: 99%
“…The partial DNA fragments from GM maize or rice were detected in the blood and intestinal contents [ 24 , 25 ]. Guo et al (2018) observed the existence of bovine and equine DNA in milk, yogurt, and other dairy products using one triplex real-time PCR [ 26 ]. Our results also confirmed that the transgenic hLZ DNA and endogenous reference gene could be detected in fresh goat milk samples, and the developed method could be further used for the detection of the transgene content in the goat milk products.…”
Section: Resultsmentioning
confidence: 99%